2013
DOI: 10.1159/000354784
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Vasotocin Neuronal Phenotype and Interspecific Cooperative Behaviour

Abstract: The nonapeptide arginine vasotocin (AVT) and its mammalian homologue arginine vasopressin are well known for their role in the modulation of several intraspecific social behaviours, such as social approach/withdrawal and aggression. Recently, we suggested that AVT might also be important in the regulation of interspecific social behaviours as it modulates interspecific cooperative behaviours in the Indo-Pacific bluestreak cleaner wrasse Labroides dimidiatus. AVT injections decreased cleaners' propensity to eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The vasotocin system of the Mozambique tilapia is restricted to the POA where parvocellular, magnocellular and gigantocellular AVT-ir cells can be recognized forming three distinct populations (pPOA, mPOA and gPOA) that follow a distribution previously described for other teleost [Goodson and Bass, 2000;Miranda et al, 2003;Lema and Nevitt, 2004;Maruska et al, 2007;Dewan et al, 2008;Maruska, 2009;Mendonça et al, 2013].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The vasotocin system of the Mozambique tilapia is restricted to the POA where parvocellular, magnocellular and gigantocellular AVT-ir cells can be recognized forming three distinct populations (pPOA, mPOA and gPOA) that follow a distribution previously described for other teleost [Goodson and Bass, 2000;Miranda et al, 2003;Lema and Nevitt, 2004;Maruska et al, 2007;Dewan et al, 2008;Maruska, 2009;Mendonça et al, 2013].…”
Section: Discussionmentioning
confidence: 66%
“…No stained neurons were observed, thus confirming the specificity of the antibody used. Other studies had already shown this antibody specificity for different species, including another cichlid species [Maruska et al, 2007;Dewan et al, 2008;Maruska, 2009;Mendonça et al, 2013].…”
Section: Immunocytochemistrymentioning
confidence: 60%
See 2 more Smart Citations
“…AVT regulation of social behavior has been studied extensively, albeit almost exclusively in males, where it has functionally been shown to promote spawning [107][108][109] , mate guarding or other forms of conspecific aggression/avoidance 43,108,[110][111][112][113][114][115] , social communication 116 , social preference 117 , and approach behavior 118 . Few studies have functionally examined IT involvement in teleost social behavior and again, those which have are exclusive to males.…”
Section: Cc-by-nc-ndmentioning
confidence: 99%